2011
DOI: 10.1155/2011/481427
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Increases Insulin Content and Basal Secretion in Pancreatic Islets in Type 1 Diabetic Mice

Abstract: Exercise appears to improve glycemic control for people with type 1 diabetes (T1D). However, the mechanism responsible for this improvement is unknown. We hypothesized that exercise has a direct effect on the insulin-producing islets. Eight-week-old mice were divided into four groups: sedentary diabetic, exercised diabetic, sedentary control, and exercised control. The exercised groups participated in voluntary wheel running for 6 weeks. When compared to the control groups, the islet density, islet diameter, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 41 publications
(49 reference statements)
5
52
0
4
Order By: Relevance
“…Many beneficial effects of exercise such as increasing insulin sensitivity, improved glucose uptake and alleviating diabet complications in diabetic animals and patients are reported. [4][5][6][7][8] Exercise is a modifiable behavioral factor which can produce several beneficial effects, including improved cardiac functions and diabetes complications. 9 Exercise training has been reported to increase SOD 10,11 and also partially reverses oxidative stress in the brains of ethanol-exposed rats.…”
Section: Introductionmentioning
confidence: 99%
“…Many beneficial effects of exercise such as increasing insulin sensitivity, improved glucose uptake and alleviating diabet complications in diabetic animals and patients are reported. [4][5][6][7][8] Exercise is a modifiable behavioral factor which can produce several beneficial effects, including improved cardiac functions and diabetes complications. 9 Exercise training has been reported to increase SOD 10,11 and also partially reverses oxidative stress in the brains of ethanol-exposed rats.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al 10 observed that trained groups, independent of performing acute physical activity, presented greater insulin content in their pancreatic islets. Huang et al 11 also observed an increase in total insulin content in diabetic type I rats. This difference between our and other studies can be due to the pattern of exercise and/or exhaustion protocol adopted during training and acute exercise session, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, an improvement in insulin secretion capacity was observed in isolated pancreatic islets, stimulated with high glucose concentration, from rats submitted to swimming training for 8 weeks 10 and in the secretion stimulated by lower glucose concentration in type I diabetic rats. 11 It was also identified that 8 weeks of treadmill running activated growth pathways and cell survival in pancreatic islets, 12 increased anaplerotic enzyme activity 13 and the mediator agent responsible for higher insulin secretory capacity induced by exercise training would be interleucine 6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, training is of great importance to control diabetes by significantly raising the energy needs of the organism, thus requiring significant acute changes in cellular metabolism and neuroendocrine control 13 . Additionally, there is evidence that physical training is important to increase insulin content, promoting greater secretion of this hormone in isolated pancreatic islets in patients with diabetes mellitus, type 1 14 .…”
Section: Introductionmentioning
confidence: 99%